Antibacterial and antioxidant potential of ethyl acetate extract from Streptomyces AIA12 and AIA17 isolated from gut of Chanos chanos (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Kurnianto MA, Kusumaningrum HD, Lioe HN, Chasanah E. 2021. Antibacterial and antioxidant potential of ethyl acetate extract from Streptomyces AIA12 and AIA17 isolated from gut of Chanos chanos. Biodiversitas 22: 3196-3206. Streptomyces has been recognized as a promising and productive source of antibacterial and antioxidant compounds. The phenotypic and genomic characterizations indicated AIA12 and AIA17 are closely related to the S. globisporus ARGB01 and S. misionensis S1-SC15, respectively. Incubation on yeast-malt extract broth for nine days (AIA12) and 11 days (AIA17) proved to be the best growth medium and optimum antibacterial production time for these two strains. Crude-extract of extracellular secondary metabolites, obtained by ethyl acetate extraction, demonstrated broad-spectrum inhibitory activity against Pseudomonas aeruginosa InaCC B52, Staphylococcus aureus ATCC 25923, Bacillus cereus ATCC 10876, Escherichia coli ATCC 25922, Salmonella Typhimurium ATCC 14028, and Listeria monocytogenes with minimum inhibitory and minimum bactericidal concentrations from 2.5 to 0.31 and 5.0 to 0.31 mg mL-1, respectively. Evaluation of antioxidant showed AIA17 crude-extract had moderate DPPH scavenging and antioxidant activities of 65.122% ± 0.56 and 28.178 ± 0.24 mg ascorbic acid equivalent antioxidant capacity (AEAC g-1), respectively. The identification of compounds through profiling with RP-HPLC showed optimum absorbance at 210 and 214 nm, which showed the presence of peptide groups in the constituent compounds' molecular structure. These findings indicate that Chanos chanos-derived Streptomyces produces valuable bioactive compounds with various promising biological activities.
Keywords: actinobacteria; antimicrobial; estuarine fish; gut-microbiota; milkfish